Pengaruh Teams Games Tournament Berbantuan Media Sticky Notes Terhadap Keterampilan Berpikir Kritis Siswa Sekolah Dasar - Erlynda Runtut Bela Vista; Angga Setiawan; Wahyu Nugroho (Jurnal Riset Madrasah Ibtidaiyah, 2023)
Education is an effort to help individuals in developing themselves. The development of science affects the existence of a systematic, critical way of learning so it is necessary to think in a directed and clear manner with the active involvement of students in learning. This research was conducted by researchers because they wanted to try to do learning by applying the Teams Games Tournament model with the help of sticky notes media with the conventional model with the help of image media in order to see a specific comparison of students' critical thinking. A research method is a quantitative approach in the form of a nonequivalent pretest and posttest control group design. The sample was from all the fourth-grade students of Az-Zahro Islamic Elementary School which amounted to 12 people and the fourth-grade students of SDN 2 Gamping 16 people. Data were obtained from students by working on pretest and posttest questions in the form of description questions totaling 10 questions. After analyzing the collected data, the researcher conducted a hypothesis test with the intention of seeing the difference from the treatment carried out. Hypothesis test analysis data obtained 0.000 <0.05 so Ha is accepted and H0 is rejected. The researcher concludes that there is a positive impact of the Teams Games Tournament (TGT) model assisted by sticky notes media on students' critical thinking skills that increase and are enthusiasm in learning activities. The increase in students' critical thinking is also known from the average post-test results of the experimental class students 91 and the control class average of 81.